Recent Developments and Challenges in Hybrid Solid Electrolytes for Lithium-Ion Batteries - Han, Lu; Lehmann, Michelle L.; Zhu, Jiadeng; Liu, Tianyi; Zhou, Zhengping; Tang, Xiaomin; Heish, Chien-Te; Sokolov, Alexei P.; Cao, Pengfei; Chen, Xi Chelsea; Saito, Tomonori (Frontiers in Energy Research, 2020)
Lithium-ion batteries (LIBs) have attracted worldwide research interest due to their high energy density and long cycle life. Solid-state LIBs improve the safety of conventional liquid-based LIBs by replacing the flammable organic electrolytes with a solid electrolyte. Among the various types of solid electrolytes, hybrid solid electrolytes (HSEs) demonstrate great promise to achieve high ionic conductivity, reduced interfacial resistance between the electrolyte and electrodes, mechanical robustness, and excellent processability due to the combined advantages of both polymer and inorganic electrolyte. This article summarizes recent developments in HSEs for LIBs. Approaches for the preparation of hybrid electrolytes and current understanding of ion-transport mechanisms are discussed. The main challenges including unsatisfactory ionic conductivity and perspectives of HSEs for LIBs are highlighted for future development. The present review provides insights into HSE development to allow a more efficient and target-oriented future endeavor on achieving high-performance solid-state LIBs.